Soursop leaf extract increases neuroglia and hepatic degeneration in female rats - Ety Sri Handayani; Zainuri Sabta Nugraha; Prilly i Raleka Pahlevawati (Faculty of Medicine, Universitas Trisakti, 2015)
BACKGROUNDSoursop leaf contains annonaceous acetogenins and alkaloids. Theacetogenins act as inhibitors of mitochondrial complex I, suppress ATPproduction and cause cell degeneration, whereas the alkaloids act asneurotoxins. Neuronal degeneration will be followed by an increase inneuroglia (gliosis). Hepatic clear cell foci represent the morphology of liverdegeneration. The purpose of this study was to evaluate the effect of soursopleaf extract on number of neuroglia brain gliosis and hepatic clear cells infemale rats.METHODSThis study was an experimental study with a post-test only control groupdesign. Ten female Sprague-Dawley strain rats were divided into one controland one treatment group. The control group was gavaged with distilled water,while the treatment group was gavaged with aqueous soursop leaf extract ata dose of 1000 mg/kgBW/day for 90 days. Rat brain tissue samples weretaken at day 91 with a transcardial perfusion technique. The number ofneuroglia in rat cerebral cortex, hippocampus, substantia nigra, and nucleusaccumbens and the number of hepatic clear cells were determined.Independent t-test was used to examine the differences in the numbers ofneuroglia and hepatic clear cells between control and treatment groupsRESULTSThe results of independent t-test analysis found a significant difference inthe number of neuroglia in the cerebral cortex (p=0.015) and nucleusaccumbens of the rats (p=0.030), and significant differences in the numberof hepatic clear cells (p=0.029).CONCLUSIONSAqueous soursop leaf extract orally increases neuroglia of the cerebral cortexand nucleus accumbens, and hepatic degeneration in female rats.